Elephants around the world - Johnson, Sylvia A.; Pajot, Anne Marie; Matte, L'Enc. (Minneapolis : Carolrhoda Books, 1977)
A young boy learns about elephants from a visit to the zoo, attending the circus, and reading at home.
Original edition published under title: Les elephants.
Keywords: Elephants -- Juvenile literature; Elephants